The Role of Family and the Role of Teachers in Reproductive Health Literacy of Adolescent Girls in Coastal Areas in Iwoimendaa District, Kolaka Regency - Aisyah Alimuddin, Siti; Rahmawati, Rahmawati; Umi Nurlila, Ratna (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: According to data from the Iwoimendaa Health Center, from July to December 2023, there were 9 teenagers who became pregnant outside of marriage. In addition, some women do not pay attention to their reproductive system so that this condition causes disorders in women's reproduction, both in the form of unpleasant odors and sexually transmitted infections. Based on this, researchers are interested in conducting research on the Role of the Family and the Role of Teachers with Reproductive Health Literacy of Adolescent Girls in Coastal Areas in Iwoimendaa District, Kolaka Regency. Method: Analytical quantitative research with Cross Sectional Study design, independent and dependent variables are measured at the same time. The population is all female teenagers at State Islamic High School 2 Kolaka totaling 180 people and a sample of 125 teenagers, sample determination using the Slovin formula. Result: The test of the closeness of the relationship shows a phi value = 0.076, which means that there is a very weak relationship between the role of the family and a phi value = 0.535, which means that there is a moderate relationship between the role of teachers and health literacy of adolescent girls in the coastal area of ​​Iwoimendaa sub-district, Kolaka district. Conclusion: There is a relationship between the role of the family and the role of teachers with health literacy of adolescent girls in the coastal area of Iwoimendaa sub-district, Kolaka district.